PERANAN ORANG TUA DALAM MENINGKATKAN PARTISIPASI ANAK PENDIDIKAN 12 TAHUN DI DESA BERANGAS KECAMATAN PULAU LAUT TIMUR KABUPATEN KOTABARU - Herlinayani Herlinayani (Universitas Lambung Mangkurat, 2013)
In principle, the government's efforts to continue to advance education is as a part of 12 years educational development in Berangas village, East Pulau Laut district of Kotabaru regency. By requiring children to study up to 12 years, it is hoped that they will be able to find out what steps should be taken to implement totally. The approach used in this study was a qualitative approach with a case study. Sources of data were parents, students, principals, teachers and school committee as well as documents relating to the school and Berangas village. The results revealed that: (1) The role of 12 years education in Berangas village, East Pulau Laut district of Kotabaru regency, clarifies that this policy is made to develop education and improve the human quality in Indonesia, (2) the parents’ role in 12 years educationin Berangas village, East Pulau Laut district of Kotabaru regency finds a lot of advantages and disadvantages. It can be viewed from educational equity and completion of 12 years education, (3) The impact of free education can be measured by several variables including the completion of 12 years education in Berangas village, as well as schools’ quality improvement and the extent of the increasing participation of children to education, (4) The constraints of 12 years education in Berangas village did not run well; therefore, this policy has an impact on the achievement of 12 years education.Keywords: Parents’ Role, Children Participation